The Effect of Smart Constructive Games on Visual-Spatial Development in Preschool Children - Abul Hasani, Rasool; Niknejad, Shabnam (International Journal of Education and Cognitive Sciences, 2025)
Purpose: This study aimed to investigate the effect of smart game-based interventions on visual-spatial development in preschool children. Methods and Materials: A quasi-experimental pretest-posttest design with a control group was employed. The sample consisted of 30 preschool children selected through cluster random sampling from two preschools in Tehran, with 15 participants assigned to the experimental group and 15 to the control group. The experimental group participated in eight structured smart game sessions, while the control group received no intervention. Visual-spatial development was assessed using the 51-item Visual-Spatial Development Questionnaire (Wachs, 2014), which includes subscales for sensory and bodily awareness, spatial localization, body-environment interaction, spatial maintenance, logical visual reasoning, and representational thinking. Data analysis was conducted using multivariate analysis of covariance (MANCOVA) to examine the differences between groups while controlling for pretest scores. Findings: The results indicated significant improvements in all visual-spatial subscales among children in the experimental group compared to the control group. Sensory and bodily awareness (F = 49.81, p < 0.01), spatial localization (F = 32.58, p < 0.01), body-environment interaction (F = 269.3, p < 0.01), spatial maintenance (F = 71.72, p < 0.01), logical visual reasoning (F = 173.4, p < 0.01), and representational thinking (F = 184.9, p < 0.01) all showed significant increases. The total visual-spatial development score also significantly improved (F = 839.01, p < 0.01), confirming the effectiveness of smart games in enhancing spatial cognitive abilities. Conclusion: The findings suggest that smart game-based interventions are highly effective in fostering visual-spatial development in preschool children. The integration of interactive, structured smart play in early childhood education can significantly enhance children's cognitive abilities, particularly in spatial reasoning and problem-solving skills.